Long-run price performance of local and dual class IPOs in alternative investment market - Abdul Wahid; Muhammad Zubair Mumtaz (Zbornik radova Ekonomskog fakulteta u Rijeci : časopis za ekonomsku teoriju i praksu, 2020)
Earlier studies document that IPOs are underpriced in the short-run and underperformed in the long-run. In almost all studies, researchers analyze the IPO performance using the dataset from highly liquid markets. However, the pricing behavior of IPOs in the Alternative Investment Market (AIM) is different. There is a reason to expect the price performance of IPOs in the AIM to be significantly different from IPO performance in traditional markets mainly because of the diminished liquidity of AIM offerings as well as the meager disclosures required in comparison to traditional markets. To test our propositions, we select 292 IPOs listed on AIM during the period between 2001 and 2016 and apply the Extreme Bound Analysis (EBA) to determine the factors that cause longer-term performance. This study reports that investors in the alternative markets earn significant positive returns if the stock is held for three years, and the price variation is dependent upon the firm size. This illustrates that investment in small-sized firms seems more profitable as compared to those of large-sized firms in the AIM. Moreover, this study examines statistical evidence bearing on the question of whether early investors in IPOs can expect abnormal excess returns in the long-run.